2021
DOI: 10.1136/heartjnl-2021-319338
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the pharmacological management of atrial fibrillation in UK general practice 2008–2018

Abstract: ObjectiveThe pharmacological management of atrial fibrillation (AF) comprises anticoagulation, for stroke prophylaxis, and rate or rhythm control drugs to alleviate symptoms and prevent heart failure. The aim of this study was to investigate trends in the proportion of patients with AF prescribed pharmacological therapies in the UK between 2008 and 2018.MethodsEleven sequential cross-sectional analyses were performed yearly from 2008 to 2018. Data were derived from an anonymised UK primary care database. Outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Our findings are consistent with most studies that investigated anticoagulation in patients with AF, 11 , 12 , 13 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 although they generally only reported crude proportions instead of PDCs to evaluate OAC use. As PDC itself is a metric for evaluating medication adherence and the increasing PDC with time was only observed in patients with a high baseline CHA 2 DS 2 -VASc score, our results suggest that OACs were increasingly prescribed to patients for whom this was indeed indicated.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are consistent with most studies that investigated anticoagulation in patients with AF, 11 , 12 , 13 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 although they generally only reported crude proportions instead of PDCs to evaluate OAC use. As PDC itself is a metric for evaluating medication adherence and the increasing PDC with time was only observed in patients with a high baseline CHA 2 DS 2 -VASc score, our results suggest that OACs were increasingly prescribed to patients for whom this was indeed indicated.…”
Section: Discussionsupporting
confidence: 91%
“…Although previous studies have described prescribing trends of antihypertensive drugs in UK primary care practices, these trends were reported for specific patient populations, indications, drug classes, or over short time periods 7 23–37. As such, there was a gap in the literature for a comprehensive assessment of the prescribing practices in primary care settings over time.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study was conducted to identify the number of eligible AF patients in the general population. Given that rhythm control therapy is rarely conducted in the UK, 14 our early rhythm control cohort was approximately half of the EAST-AFNET4 population and therefore underpowered for efficacy studies.…”
Section: Discussionmentioning
confidence: 99%
“…For one, we capture a part of the whole population since we focused on optimal data quality and excluded those without Additionally, a recent study using a database of primary care data in the UK from 2008 to 2018 showed that OAC use in the UK was around 43% and only recently increased to 71.6%. 14 Nevertheless, our propensity-score matched analysis provides an estimate of the of early rhythm control therapy when the rates of OAC are similarly high.…”
Section: Arrhythmias and Sudden Deathmentioning
confidence: 99%